Expression of LAG-3 on B-lymphocytes as a marker for prediction of response to therapy in patients with chronic lymphocytic leukemia - O. N. Selyutina; I. B. Lysenko; N. K. Guskova; I. A. Novikova; E. Yu. Zlatnik; T. F. Pushkareva; N. V. Nikolaeva; I. A. Kamaeva; N. Yu. Samaneva; E. A. Kapuza (Сибирский онкологический журнал, 2023)
Purpose: to study the level of LAG-3 expression on B-lymphocytes and the feasibility of using it as a marker for predicting response to therapy in patients with chronic lymphocytic leukemia (CLL).Material and Methods. The study included 40 patients with newly diagnosed CLL. All patients were divided into two groups: group I: patients with Binet stage A, who did not receive therapy and group II: patients with Binet stage C, who received immunochemotherapy in RB and FCR regimes. According to the treatment regimen and hematological response to therapy, 4 subgroups were distinguished: IIA-RB, IIA-FCR, IIB-RB, and IIB-FCR. The control group consisted of 20 people matched in age and gender without cancer. The immunophenotype, level of B-lymphocytes, LAG-3 expression, and the minimal residual disease in group II after the 6th course of immunochemotherapy were initially determined in all groups by flow cytometry. The data were evaluated using Statistica 13.0.Results. Compared to the control group, the LAG-3 expression on B-lymphocytes was found in all groups of CLL patients before treatment. The expression level was higher in patients with Binet stage C than in patients with Binet stage. The data demonstrated differences in the level of LAG-3 expression in patients with different hematological responses to therapy. The initially higher level of LAG-3 expression on B-lymphocytes was observed in patients with Binet stage C CLL with an unfavorable response to therapy. A good hematological response was found can be achieved at the level of LAG-3 expression within 14.57 ± 0.66 % regardless of the therapy regimen, and unfavorable response to therapy at the level of 41.95 ± 1.62 %.Conclusion. The initial level of LAG-3 expression on B-lymphocytes in patients with CLL can be used as a marker for predicting and monitoring response to treatment, regardless of the immunochemotherapy regimen used.